A New Mobile Malware Classification for Camera Exploitation based on System Call and Permission - Madihah Mohd Saudi; Farida Hazwani Mohd Ridzuan; Nurlida Basir; Sakinah Ali Pitchay; Nur Fatin Nabila Mohd Rafei Heng; Zahari, LH (Int Assoc Engineers-Iaeng, 2024)
Currently, there are many attacks and exploitation to Android smartphones by the attackers all over the world. These attacks are based on profit and caused loss of money and productivity to the victim. This exploitation can be done via camera, SMS, call, audio, image or location exploitation by attacking the system call, permission or API inside the Android smartphone. Therefore, this paper presents 32 mobile malware classification based on system call and permission to detect camera exploitation for Android smartphone. The experiment was conducted in a controlled lab environment, by applying reverse engineering with 5560 training dataset from Drebin, where both static and dynamic analyses were used to identify and extract the permission and system call from the mobile applications (apps). These 32 classification have been evaluated with 500 mobile apps from Google Play Store and 19 mobile apps matched with the classification. This new classification can be used as the database and input for the development of new mobile malware detection model for camera exploitation.